Quine in Dialogue - Follesdal, Dagfinn (Harvard University Press, 2008)
Quine was one of the 20th century's great philosophers. This volume begins with a number of interviews Quine gave about his perspectives on 20th-century logic, science and philosophy, the ideas of others, and philosophy generally. Also included are his most important articles, reviews, and comments on other philosophers, from Carnap to Strawson.